High accuracy thermal conductivity measurement of aqueous cryoprotective agents and semi-rigid biological tissues using a microfabricated thermal sensor - Liang, Xin M. (Sci Rep, 2015)
An improved thermal-needle approach for accurate and fast measurement of thermal conductivity of aqueous and soft biomaterials was developed using microfabricated thermal conductivity sensors. This microscopic measuring device was comprehensively characterized at temperatures from 0 °C to 40 °C. Despite the previous belief, system calibration constant was observed to be highly temperature-dependent. Dynamic thermal conductivity response during cooling (40 °C to –40 °C) was observed using the miniaturized single tip sensor for various concentrations of CPAs, i.e., glycerol, ethylene glycol and dimethyl sulfoxide. Chicken breast, chicken skin, porcine limb, and bovine liver were assayed to investigate the effect of anatomical heterogeneity on thermal conductivity using the arrayed multi-tip sensor at 20 °C. Experimental results revealed distinctive differences in localized thermal conductivity, which suggests the use of approximated or constant property values is expected to bring about results with largely inflated uncertainties when investigating bio-heat transfer mechanisms and/or performing sophisticated thermal modeling with complex biological tissues. Overall, the presented micro thermal sensor with automated data analysis algorithm is a promising approach for direct thermal conductivity measurement of aqueous solutions and soft biomaterials and is of great value to cryopreservation of tissues, hyperthermia or cryogenic, and other thermal-based clinical diagnostics and treatments.